PENEGAKAN KODE ETIK PROFESI SEBAGAI UPAYA MEMBANGUN CITRA JABATAN NOTARIS DI WILAYAH DAERAH ISTIMEWA YOGYAKARTA - , YAOMI EVADA, Sigid Riyanto, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine what efforts are made Indonesian Notaries Association (INI) in an effort to build the image of Notary office and constraints obtained Indonesian Notaries Association (INI) in an effort to build the image of the Notary office. The method of writing in this thesis is empirical juridical. The data that is used are the primary data and secondary data. Secondary data is obtained by literature study, whereas the primary data that is obtained through interviews. Interviews are conducted against the informant and the respondent from the Office of the Ministry of Justice and Human Rights and Notaries and Notary Association Executive of the Daerah Istimewa of Yogyakarta Indonesia. The analysis in the study is conducted using qualitative methods, i.e. data obtained qualitatively analyzed and presented descriptively. As for the deduction is done by using the deductive method of thought, which it concludes the results of special research. Based on the use of this method is expected to obtain a clear and comprehensive picture about the suitability of the conceptual foundation that is used with the title of the study. During this time efforts are made to enforce the Code of Professional Notary in Daerah Istimewa of Yogyakarta by the Organization of Indonesian Notaries Association (INI) that is conducted by the Assembly and the Council of Honorary Trustees are not always done well, so there are frequent violations of the Code. Violations by the Public Notary that is resulting image has not been fully considered both in the public eye. Implementation of Enforcement image Notary has not run well because of sanctions that are not firm and lack of communication with the Organization of Notaries so that less optimal enforcement of the Code of Ethics. Also sometimes a Notary Honorary Board member of Notaries whitewashing Or in other words mutual hesitate between the Notary making it difficult in the enforcement of Image Occupation and Professions Code of Ethics Notary.